2014
DOI: 10.1186/preaccept-4212075851409303
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing identifies novel and recurrent mutations in GJA8 and CRYGD associated with inherited cataract

Abstract: Background: Inherited cataract is a clinically important and genetically heterogeneous cause of visual impairment. Typically, it presents at an early age with or without other ocular/systemic signs and lacks clear phenotype-genotype correlation rendering both clinical classification and molecular diagnosis challenging. Here we have utilized trio-based whole exome sequencing to discover mutations in candidate genes underlying autosomal dominant cataract segregating in three nuclear families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
(28 reference statements)
1
18
0
Order By: Relevance
“…The red band denotes the mutation p.H277Y reported in our present study. (b) Multiple sequence alignment of a section of the Cx50 amino acid sequence (codons 268-287) from ten different species, indicating that histidine at position 277 (red) is highly conserved among Cx50 members from a variety of species inherited cataracts lack clear genotype-phenotype correlation rendering both clinical classification and molecular diagnosis challenging [11]. There is only one possible genotypephenotype correlation that we found after a comprehensive literature search and careful comparison: the Cx50 mutations associated with congenital cataract-microcornea syndrome were exclusively located in first transmembrane domain (M1) and second extracellular loop (E2) (Supplementary Table 2, Online Resource 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The red band denotes the mutation p.H277Y reported in our present study. (b) Multiple sequence alignment of a section of the Cx50 amino acid sequence (codons 268-287) from ten different species, indicating that histidine at position 277 (red) is highly conserved among Cx50 members from a variety of species inherited cataracts lack clear genotype-phenotype correlation rendering both clinical classification and molecular diagnosis challenging [11]. There is only one possible genotypephenotype correlation that we found after a comprehensive literature search and careful comparison: the Cx50 mutations associated with congenital cataract-microcornea syndrome were exclusively located in first transmembrane domain (M1) and second extracellular loop (E2) (Supplementary Table 2, Online Resource 1).…”
Section: Discussionmentioning
confidence: 99%
“…To Electronic supplementary material The online version of this article (doi:10.1007/s00417-015-3019-x) contains supplementary material, which is available to authorized users. date, at least 30 independent loci and 18 genes on different chromosomes have been associated with isolated congenital or infantile cataract [8][9][10][11]. Of the known mutant genes in cataract families, approximately half involve mutations in crystallins (CRYAA, CRYAB, CRYBA, CRYBB, CRYGC, CRYGD, CRYGS), about a quarter involve mutations in lens specific connexins (Cx43, Cx46, and Cx50), and the remainder include: mutations in major intrinsic protein (MIP) or aquaporin-0 (AQP0), beaded filament structural proteins-2 (BFSP2), paired-like homeodomain transcription factor-3 (PITX3), avian musculoaponeurotic fibrosarcoma (MAF), heat shock transcription factor-4 (HSF4), chromatin modifying protein-4B (CHMP4B), lens intrinsic membrane protein 2 (LIM2), and Eph-receptor type-A2 (EPHA2E) [8,9,[11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The strongest signal for interaction in relation to retinopathy was observed for GJA8. Deletion of this gene has been associated with eye abnormalities and retinopathy of prematurity in premature infants, inherited cataracts, visual impairment and cardiac defects and eye abnormalities [26][27][28] . TCF7L2 is a known diabetes locus and its association with progression to retinopathy has been previously established 29 .…”
Section: Discussionmentioning
confidence: 99%
“…It was revealed that the substitution of proline with threonine changes the structure of the amino acid at position 24 from a pyrrole ring to a nonpyrrole ring (Figure 4). After proline was changed to threonine, there was a branched beta carbon atom in the side chain of the threonine, making the beta-chain tend to extend rather than fold back, which may affect the correct folding of the protein material [2,33]. Previous studies have shown that the solubility of the p.P24T mutant protein is significantly lower than that of the wild type CRYGD protein, which may lead to decreased solubility and the aggregation of polymer material [2,33].…”
Section: Discussionmentioning
confidence: 99%